Seasonal prevalence and pathology of hepatic parasitic afflictions of Gaddi (breed) goats in North Western Himalayas. Issue 1 (2nd January 2021) - Moudgil, Aman D.; Asrani, R. K.; Sharma, Rakshita; Sharma, Devina; Agnihotri, R. K.
ABSTRACT: The present study aimed to detect the prevalence and to assess histopathological alterations incriminated to parasitic stages in the liver of Gaddi (breed) goats of the Kangra valley, Himachal Pradesh, India. Out of 107 goats examined (57 males and 50 females), 17 (15.88%) evinced the presence of individual or mixed parasitic infections. The highest prevalence was recorded in winter (25.71%) followed by monsoon (14.28%) and summer seasons (8.11%). Amongst individual parasitic infections, hydatidosis (7.01%) showed the highest prevalence in males followed by distomatosis (3.52%). On the other hand, in females hydatidosis and distomatosis (fasciolosis and dicrocoeliosis) exhibited 4% prevalence each. Concurrent hydatidosis and distomatosis were the most common mixed hepatic parasitic infections encountered in both males (8.77%) and females (4%) examined. The samples of the infected liver subjected to histopathology exhibited the presence of multiple cysts of variable sizes containing outer lining epithelium surrounded by the zone of lymphocytic infiltration. The present study highlighted the observation of the diseases of emerging public health concern and require generation of awareness amongst the shepherds, people working in abattoirs as well as consumers about the seasonal preponderance, transmission and ill effects of the diseases.